High-sensitivity CRP discriminates HNF1A-MODY from other subtypes of diabetes. - McDonald, T; Shields, B; Lawry, J; Owen, K; Gloyn, A; Ellard, S; Hattersley, A (2011)
OBJECTIVE: Maturity-onset diabetes of the young (MODY) as a result of mutations in hepatocyte nuclear factor 1-α (HNF1A) is often misdiagnosed as type 1 diabetes or type 2 diabetes. Recent work has shown that high-sensitivity C-reactive protein (hs-CRP) levels are lower in HNF1A-MODY than type 1 diabetes, type 2 diabetes, or glucokinase (GCK)-MODY. We aim to replicate these findings in larger numbers and other MODY subtypes. RESEARCH DESIGN AND METHODS: hs-CRP levels were assessed in 750 patients (220 HNF1A, 245 GCK, 54 HNF4-α [HNF4A], 21 HNF1-β (HNF1B), 53 type 1 diabetes, and 157 type 2 diabetes). RESULTS: hs-CRP was lower in HNF1A-MODY (median [IQR] 0.3 [0.1-0.6] mg/L) than type 2 diabetes (1.40 [0.60-3.45] mg/L; P < 0.001) and type 1 diabetes (1.10 [0.50-1.85] mg/L; P < 0.001), HNF4A-MODY (1.45 [0.46-2.88] mg/L; P < 0.001), GCK-MODY (0.60 [0.30-1.80] mg/L; P < 0.001), and HNF1B-MODY (0.60 [0.10-2.8] mg/L; P = 0.07). hs-CRP discriminated HNF1A-MODY from type 2 diabetes with hs-CRP <0.75 mg/L showing 79% sensitivity and 70% specificity (receiver operating characteristic area under the curve = 0.84). CONCLUSIONS: hs-CRP levels are lower in HNF1A-MODY than other forms of diabetes and may be used as a biomarker to select patients for diagnostic HNF1A genetic testing.